Devonian Crustal Stretching in the Northern Tasmanides (Australia) and Implications for Oroclinal Bending. Issue 8 (29th August 2018) - Abdullah, Rashed; Rosenbaum, Gideon
Abstract: The Tasmanides in eastern Australia exhibit a number of orogenic curvatures (oroclines), and possibly, a continental‐scale bend that defines the continuation of the Delamerian Orogen with the Thomson Orogen. We provide an insight into the geodynamic processes associated with the origin of this orocline. We present interpretations of seismic reflection profiles and potential field data from the Thomson Orogen, which provide information on the crustal architecture and unravel major structures and kinematic relationships. Results show that a large area in the northern Tasmanides is underlain by thinned crust, bounded in the north and south by E‐W trending geophysical features with apparent sinistral and dextral sense of kinematics, respectively. Within the highly extended crust of the Thomson Orogen, there is evidence for widespread Devonian basins bounded by normal faults. In stark contrast to the southern Tasmanides, where rocks show evidence for an earlier (Silurian) episode of extension and Devonian contractional deformation, no evidence for Silurian synrift sedimentation is observed in the Thomson Orogen. Evidence for E‐W trending sinistral and dextral crustal‐scale shear zones in the northern and southern boundaries of the Thomson Orogen, respectively, may represent tear faults, which were active during the Early Devonian and were possibly accompanied by tear‐related magmatism. We suggest that crustal stretching in the northern Tasmanides was associated with Devonian back‐arc extension in response to trench retreat, bounded by zones of slab‐tearing and crustal segmentation that ultimately led to the development of the Delamerian‐Thomson Orocline. Key Points: Continuation of the Ross‐Delamerian Orogen into the northern Tasmanides of eastern Australia is marked by an orogenic‐scale bending The northern Tasmanides was subjected to bulk crustal thinning and back‐arc extension in response to subduction roll‐back during Devonian Orogenic‐scale bending in the Delamerian‐Thomson belt was possibly controlled by back‐arc extension and slab‐tearing